PENINGKATAN KETERAMPILAN PERANCANGAN DAN PEMBUATAN GANTUNGAN SELANG AIR MINIMALIS - I Wayan Sukania; Lamto Widodo; Lithrone Laricha S; Jennifer Juyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Knowledge and skills in product design and manufacture are still very minimal experienced by most of the students of the Non-Formal Pasraman Kertajaya Tangerang. This is because all students come from general schools. The pasraman curriculum only emphasizes increasing knowledge and insight into attitudes and noble character. The practice given is about dancing skills, making worship facilities and skills in chanting holy songs and similar skills. Discussions with students and teachers produce data on students' needs to increase knowledge, insight and skills, especially designing and manufacturing products through basic welding techniques. Welding skills are needed as a provision for entrepreneurship in the field of welding. The implementation of PKM is carried out in 2 stages, namely the debriefing stage and the practical stage in the welding workshop. The debriefing produces various minimalist water hose hanger concepts according to the specified criteria. The practice is carried out in groups to realize the existing designs. Practical activities provide experience measuring materials, cutting, sanding, grinding, rolling, welding, and painting and teamwork. The output of the training resulted in a minimalist hose hanger concept and prototype. Debriefing and practice can increase market research knowledge by 80%, increase 70% in understanding human factors and increase 90% in understanding the stages of product design. Field practice increases experience working in groups by 50% and the ability to use welding shop equipment increases by 50%. All participants were satisfied with the instructor's guide and training materials. In general, skills training activities are called successful. ABSTRAK: Pengetahuan dan keterampilan perancangan dan pembuatan produk masih sangat minim dialami sebagian besar siswa Pasraman Non Formal Kertajaya Tangerang. Hal ini karena seluruh siswa berasal dari sekolah umum. Kurikulum pasraman hanya menekankan pada peningkatan ilmu dan wawasan sikap dan budi pekerti luhur. Praktik yang diberikan seputar keterampilan menari, membuat sarana ibadah dan keterampilan melantunkan kidung suci dan keterampilan sejenis. Diskusi dengan siswa dan guru menghasilkan data kebutuhan siswa untuk peningkatan ilmu, wawasan dan keterampilan khususnya perancangan dan pembuatan produk melalui teknik pengelasan dasar. Keterampilan mengelas diperlukan sebagai bekal berwirausaha bidang pengelasan. Pelaksanaan PKM dilakukan 2 tahap yaitu tahap pembekalan dan tahap praktik di bengkel las. Pembekalan menghasilkan berbagai konsep gantungan selang air minimalis sesuai kriteria yang ditentukan. Praktik dilaksanakan secara berkelompok mewujudkan desain yang telah ada. Kegiatan praktik memberikan pengalaman mengukur bahan, memotong, mengamplas, menggerinda, mengerol, mengelas, dan mengecat dan kerja tim. Luaran pelatihan menghasilkan konsep dan prototipe gantungan selang minimalis. Pembekalan dan praktik mampu menambah pengetahuan riset pasar sebesar 80%, peningkatan 70% pada pemahaman faktor manusia dan peningkatan 90% pada pemahaman tahapan perancangan produk. Praktik lapangan menambah pengalaman bekerja berkelompok sebesar 50% dan kemampuan menggunakan peralatan bengkel las meningkat sebesar 50%. Semua peserta puas dengan panduan instruktur dan materi pelatihan. Secara umum kegiatan pelatihan keterampilan disebut berhasil